2001
DOI: 10.1074/jbc.m102794200
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Modulation of Cytoskeletal Proteins Linking Integrins to Signaling Complexes in Spreading Cells

Abstract: Recently we showed that signaling across ␤ 3 -integrin leads to activation of calpain and formation of integrin clusters that are involved in Rac activation. The subsequent activation of Rac and Rho leads to the formation of focal complexes and focal adhesions, respectively. The goal of the present study was to determine whether different proteins link the integrin to the cytoskeleton in the different complexes. We show that talin is present in focal adhesions but not in the calpain-induced clusters. ␣-Actinin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 59 publications
1
40
0
Order By: Relevance
“…At this stage of spreading, Rac1 activity is required for the formation of lamellipodia, and mechanisms appear to exist for maintaining RhoA in an inactive form until the cells have spread to a point where RhoA-induced stress fibers and focal adhesions are required (5,6,28). Recently, we showed that one of the earliest detectable events following integrin-induced adhesion is the formation of a previously unrecognized type of integrin cluster; these clusters contain active calpain, calpain-cleaved integrin, and cytoskeletal proteins and signaling molecules not detected in the previously described focal complexes and adhesions (20,21). The clusters form upstream of Rac1 activation, and we have suggested that they allow Rac1 activation because they bring together proteins involved in integrin-induced Rac1 activation (20,21).…”
Section: Discussionmentioning
confidence: 99%
“…At this stage of spreading, Rac1 activity is required for the formation of lamellipodia, and mechanisms appear to exist for maintaining RhoA in an inactive form until the cells have spread to a point where RhoA-induced stress fibers and focal adhesions are required (5,6,28). Recently, we showed that one of the earliest detectable events following integrin-induced adhesion is the formation of a previously unrecognized type of integrin cluster; these clusters contain active calpain, calpain-cleaved integrin, and cytoskeletal proteins and signaling molecules not detected in the previously described focal complexes and adhesions (20,21). The clusters form upstream of Rac1 activation, and we have suggested that they allow Rac1 activation because they bring together proteins involved in integrin-induced Rac1 activation (20,21).…”
Section: Discussionmentioning
confidence: 99%
“…These residues are Phe 993 , Lys 994 , and Asn 996 , and they are located on the opposite side of ␣ IIb interface with ␤ 3 CT. Nevertheless, because skelemin is involved in the formation of the nascent focal adhesions regulating the cytoskeleton organization, both possibilities may enhance integrin clustering, which is essential for cell spreading, a major finding as to how skelemin regulates integrin signaling (11). If skelemin is recruited to the inactive integrin, it may contribute to the receptor activation in certain cell types because it does have some weak unclasping activity (possibility I).…”
Section: Discussionmentioning
confidence: 99%
“…Other members of this family, all associated with myosin thick filaments in skeletal and cardiac muscle, include titin (6), twitchin (7), progectin (8), myomesin-II (9), and myosin light-chain kinase (10). Based upon yeast two-hybrid, in vitro deletion/ competitive binding and in vivo transient expression studies, the integrin/skelemin interface was proposed to involve the skelemin IgC domains 4 and 5 (4,11).…”
mentioning
confidence: 99%
“…In in vitro experiments, the control DNAzyme containing binding arms with a scrambled sequence did not show any activity after treating NIH3T3 cells (Figure 1a this discrepancy, its sequence was subjected to BLAST analysis and showed the presence of a 15-residue stretch of nucleotides that was complementary to myomesin 1 (skelemin) mRNA. There is strong evidence that skelemin by interacting with cytoplasmic tail of integrin b subunits influences conversion of integrins into the activating state 33 . Therefore, we have analyzed the effect of mb1DE SC on skelemin expression in cancer cell lines (PC3, CX1.1) measured at mRNA and protein levels (data not shown).…”
Section: Mb1de Inhibits Growth Of Carcinoma Solid Tumorsmentioning
confidence: 99%